Demographic and clinical profile of patients undergoing echocardiography at a tertiary institution in central South Africa - van den Heever, E.; Botes, L.; Brown, S.C.; Smit, F.E. (SA Heart Journal, 2024)
Introduction: Worldwide cardiovascular disease is associated with substantial economic challenges and profound morbidity and mortality. Considering the dearth of information for the central region of South Africa, this study aimed to assess the profile of patients who were referred to an echocardiography laboratory at a tertiary institution. Methods: A hospital-based, observational, descriptive study was conducted. Demographic, anthropometric, socio-economic, clinical and echocardiographic data were collected. Patients were categorised by hospitalisation status and reason for referral. Standard transthoracic echocardiograms were performed. Data were analysed using standard statistical software. Results: The study population had a mean age of 51.8±17.38 years, was predominantly black (64%) with a slight female preponderance (55%). The majority of patients were from a low-socioeconomic background (H0-H2; 91%). Most patients were from the Mangaung district (37%) and the referral pattern showed that regions with more hospitals tend to refer more patients for echocardiography. Alarmingly, two-thirds of the study population were hypertensive (64%) and 57% had a body mass index exceeding 25 kg/m2. Cardiology referred most patients for echocardiography (49%) and inpatient and outpatient referrals were almost equal (48% vs 52%). Abnormal echocardiographic findings were reported in 74% of patients with myocardial dysfunction being the most significant pathology (73%). Sixty-three percent of referrals were for routine echocardiographic assessment. Conclusion: This is the first study describing the profile of patients referred for echocardiography in the central region of South Africa. Travel distances and obtainability of health services appeared to have impacted referral patterns. Specific patterns of disease related to the individual referring specialist health care services. Hospitalisation status did not influence referrals.